2001
DOI: 10.1017/s0033291701004743
|View full text |Cite
|
Sign up to set email alerts
|

A 25-year longitudinal, comparison study of the outcome of depression

Abstract: Even after 25 years, severe depressive disorders appear to have poor long-term outcomes. Patients with chronic outcomes over 15 years can improve when followed over longer periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 41 publications
3
61
1
1
Order By: Relevance
“…Studies of single disorders tend to have a shorter follow-up period, and depend on the severity of the first episode of disorder ; thus, Eaton et al (2008) followed first episodes of depression in a community sample for at least 13 years and showed that half had only a single episode, whereas 35 % had recurrent episodes and 15 % were unremitting. Brodaty et al (2001) followed depressives who had been admitted to hospital for 25 years, and showed that only 12 % had recovered and were well whereas 84 % had had recurrences. Patients attending specialist clinics for anxiety disorders have been followed for shorter periods.…”
Section: Coursementioning
confidence: 99%
“…Studies of single disorders tend to have a shorter follow-up period, and depend on the severity of the first episode of disorder ; thus, Eaton et al (2008) followed first episodes of depression in a community sample for at least 13 years and showed that half had only a single episode, whereas 35 % had recurrent episodes and 15 % were unremitting. Brodaty et al (2001) followed depressives who had been admitted to hospital for 25 years, and showed that only 12 % had recovered and were well whereas 84 % had had recurrences. Patients attending specialist clinics for anxiety disorders have been followed for shorter periods.…”
Section: Coursementioning
confidence: 99%
“…Significant numbers of people (up to 80%) who have experienced MDD will experience at least one more episode of MDD later during their lifetime, and 20% will have a chronic course of MDE lasting more than 2 years (Angst, 1986;Keller et al, 1992;Brodaty et al, 2001). …”
Section: Course and Outcome Of Mddmentioning
confidence: 99%
“…[1][2][3] Guidelines for the treatment of depression, such as those published by the Canadian Network for Mood and Anxiety Treatments (CANMAT) 5 and the National Institute for Health and Clinical Excellence (NICE) in the United Kingdom, 4 often recommend antidepressant treatment in patients with severe symptoms and outline specific risk factors supporting long-term treatment maintenance. 4,5 However, for patients who do not meet the criteria for treatment of depression, the damaging sequelae of depression are frequently compounded without treatment.…”
mentioning
confidence: 99%